# Graph 4x-6y=6 4x-6y=6
Solve for y.
Subtract 4x from both sides of the equation.
-6y=6-4x
Divide each term by -6 and simplify.
Divide each term in -6y=6-4x by -6.
-6y-6=6-6+-4x-6
Cancel the common factor of -6.
Cancel the common factor.
-6y-6=6-6+-4x-6
Divide y by 1.
y=6-6+-4x-6
y=6-6+-4x-6
Simplify each term.
Divide 6 by -6.
y=-1+-4x-6
Cancel the common factor of -4 and -6.
Factor -2 out of -4x.
y=-1+-2(2x)-6
Cancel the common factors.
Factor -2 out of -6.
y=-1+-2(2x)-2(3)
Cancel the common factor.
y=-1+-2(2x)-2⋅3
Rewrite the expression.
y=-1+2×3
y=-1+2×3
y=-1+2×3
y=-1+2×3
y=-1+2×3
y=-1+2×3
Rewrite in slope-intercept form.
The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.
y=mx+b
Reorder -1 and 2×3.
y=2×3-1
Rewrite in slope-intercept form.
y=23x-1
y=23x-1
Use the slope-intercept form to find the slope and y-intercept.
Find the values of m and b using the form y=mx+b.
m=23
b=-1
The slope of the line is the value of m, and the y-intercept is the value of b.
Slope: 23
y-intercept: -1
Slope: 23
y-intercept: -1
Any line can be graphed using two points. Select two x values, and plug them into the equation to find the corresponding y values.
Choose 0 to substitute in for x to find the ordered pair.
Replace the variable x with 0 in the expression.
f(0)=2(0)3-1
Simplify the result.
Multiply 2 by 0.
f(0)=03-1
Divide 0 by 3.
f(0)=0-1
Subtract 1 from 0.
f(0)=-1
The final answer is -1.
-1
-1
The y value at x=0 is -1.
y=-1
y=-1
Choose 3 to substitute in for x to find the ordered pair.
Replace the variable x with 3 in the expression.
f(3)=2(3)3-1
Simplify the result.
Multiply 2 by 3.
f(3)=63-1
Divide 6 by 3.
f(3)=2-1
Subtract 1 from 2.
f(3)=1
The final answer is 1.
1
1
The y value at x=3 is 1.
y=1
y=1
Create a table of the x and y values.
xy0-131
xy0-131
Graph the line using the slope and the y-intercept, or the points.
Slope: 23
y-intercept: -1
xy0-131
Graph 4x-6y=6   ## Download our App from the store

### Create a High Performed UI/UX Design from a Silicon Valley.  Scroll to top